Character Education in the Digital Era: Conceptual Analysis of Technology Integration in the Formation of Student Morals - Apri Eka Budiyono; Hendri Wibowo; Sandi Pradana (Quantum Edukatif: Jurnal Pendidikan Multidisiplin, 2024)
The digital era has significantly influenced the framework of character education, necessitating the integration of technology to enhance students' moral development. This library research explores the conceptual framework of character education in the digital age, emphasizing the role of technology in shaping students' ethical reasoning and behavior. Findings indicate that innovative tools such as gamification, virtual simulations, and personalized e-learning platforms provide engaging ways to teach moral values. However, challenges such as reduced interpersonal interactions, misinformation, and digital distractions pose risks that require balanced solutions. This study highlights the importance of incorporating media literacy and digital ethics to ensure technology complements traditional character education.